Gent morgen : 35 jaar dromen, plannen en bouwen in de stad - Van Keymeulen, Karel; De Vuyst, Wout; De Waele, Maria; Rousseau, Herman (Gent: Gent Cultuurstad, 2006)
"Karel Van Keymeulen, Wout De Vuyst, Maria De Waele, Herman Rousseau"